Treatment of persistent COVID-19 in two B-cell-depleted patients with the monoclonal antibody Sotrovimab. (2022) - Totschnig, David; Doberer, Daniel; Haberl, Renate; Wenisch, Christoph; Valipour, Arschang
Abstract: Background: Patients having undergone B-cell-depletion with anti-CD20-antibodies have a higher risk of mortality, delayed viral clearance and prolonged infection due to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). We report two cases of patients with persistent coronavirus disease 2019 (COVID-19) in association with B-cell-depletion that were treated with the monoclonal antibody Sotrovimab. Case presentation: Both patients presented with chronic symptoms of COVID-19 such as dyspnea, fatigue, and chest pain. Nasopharyngeal swabs remained positive months after the initial infection with fluctuating cycle threshold (Ct) values around 30. Both patients received a single infusion with the monoclonal SARS-CoV-2 antibody Sotrovimab, which resulted in a rapid improvement of symptoms and inflammation markers as well as negative SARS-CoV-2 swabs. A follow-up after a month showed ongoing improvement of symptoms, persistent negative SARS-CoV-2 swabs, and positive serum antibodies. Conclusion: Infusion with the monoclonal SARS-CoV-2 antibody led to rapid improvement in two patients with persistent COVID-19 after B-cell depletion. Highlights: Persistent COVID-19 can occur in B-cell depleted individuals. We successfully used the monoclonal antibody Sotrovimab to treat two such patients. Their symptoms improved significantly, and their SARS-CoV-2 swabs became negative. Improvements were ongoing at a follow-up one month later.